Thermal radiation and viscous dissipation impact on 2D MHD Williamson ternary hybrid nanofluid flow over a stretching surface - Rehman, Ali; Inc, Mustafa; Saad, Abdullah Aziz; Abas, Siti Sabariah; Sudarmozhi, K.; Khashi'ie, Najiyah Safwa (Springer, 2026)
In this research, the impact of thermal effects, viscous energy loss, and magnetic-field interaction on a Williamson ternary hybrid nanofluid (Ag, SWCNT, MWCNT) that simulates blood flow (in 2D) over an elastically moving surface is assessed. An analytical technique is developed to provide a framework for enhancing convective heat transfer and reducing streamwise resistance in high-energy systems. Obtaining semi-analytical solutions to the governing nonlinear partial differential equations within the BVPh 1.0 and BVPh 2.0 packages for Mathematica involves transforming them into ordinary differential equations via special similarity variables, applying the homotopy analysis approximating method, and achieving residuals below 10(-5) in fewer than 20 steps. The analysis reveals that the resultant average heat transfer (Nu) is over 21% due to the surface cooling heat flux, the thickening of the opaque thermal layer from thermal effects, the extension of the Eckert number, the nanofluid volumetric concentration, and the magnetic Williamson number (slowing rates). And accurately including these ternary hybrid nanofluids in biomedical wearables, blood cooling, polymer extrusion cooling, and highly oriented micro- and electronic heat exchangers for efficient simultaneous temperature and shear stress, is revealing.
Keywords: Ternary Hybrid Nanofluid; Homotopy Analysis Method; Magnetic Field; Thermal Radiation; Thermal Management